Faktor Keberhasilan Delimitasi Batas Zona Ekonomi Eksklusif (ZEE) antara Indonesia dan Filipina - Intan Fatona Maharani Putri (Andalas Institute of International Studies UNAND, 2024)
This paper discusses factors underlying the success of the Exclusive Economic Zone (EEZ) boundary delimitation between Indonesia and the Philippines. This paper uses issue-level approach from the literature on territorial disputes which focus on the interaction between territoriality and visibility factors in shaping the dynamics of territorial disputes. According to this approach, disputes over territory that is not salient in terms of its tangible/intangible value but is visible to domestic audience are more likely to be settled peacefully because the government is likely to face pressure from the domestic audience to settle the dispute and the low salience of the territory increase the possibility for peaceful settlement. This paper found that this also applies in the case of Indonesia and the Philippines. The undelimited EEZ between Indonesia and the Philippines is not salient but the increase visibility of this issue contributes to the immediate completion of boundary delimitation between the two countries peacefully.